Occurrence of intestinal parasitic contamination in selected consumed local raw vegetables and fruits in Kuantan, Pahang - Mat Yusof, Afzan; Mohammad, Mardhiah; Abdullahi, Muna Abshir; Mohamed, Zeehaida; Zakaria, Robaiza; Abdul Wahab, Ridhwan (Universiti Sains Malaysia, 2017)
Intestinal parasitic infections are one of the most common human diseases that cause serious health and economic issues in many developing and developed countries. Raw vegetables and fruits play an important role in transmitting parasites into humans. Hence, the aim of this study is to investigate the parasitological contamination of the commonly consumed selected local leafy vegetables and fruits in Kuantan, Malaysia. One kilogram of local consumed-raw vegetables and fruits were collected randomly from Kuantan wet market (Pasar Tani) during monsoon seasons (November 2014-January 2014) and dry seasons (February 2015- April 2015). Standard wet mount procedure and modified Ziehl-Neelsen stain were used for the detection of parasites. In the present study, the examination of vegetables revealed five different species of parasites. The vegetables samples collected from Kuantan’s wet market were positive for both helminths and protozoa. However, the fruits samples were negative for parasitic contamination. Pegaga was the most contaminated leafy vegetables in this study and Strongyloides was the most frequently found parasite. Furthermore, there was a high diversity in the type of observed parasites during the dry season as compared to monsoon season. Therefore, further action should be taken to reduce the occurrence of parasitic contamination in vegetables by implementing the principles of good agriculture practices and improving the water treatment efficacy.